Can UML be a system-language for embedded software? - Fernandes, João M. (2002)
The main purpose of this paper is to discuss if the Unified Modeling Language (UML) can be used as a system-level language (SLL) for specifying embedded systems, in co-design environments. The requirements that a language has to fulfil to be considered as an SLL are presented and the advantages and disadvantages of using UML as an SLL are also indicated. The contribution of this paper consists on the explicit discussion of the key issues that must be taken into account when deciding if UML is to be used in a project ss an SLL for embedded software.